Safety and effectiveness of Salvia miltiorrhiza and ligustrazine injection for acute cerebral infarction in Chinese population: a PRISMA-compliant meta-analysis - Ma, Zhuoya; Zhang, Hu; Zhao, Fen; Li, Ke; Dong, Nanhai; Sang, Wenwen (Frontiers in Pharmacology, 2024)
Background: Salvia miltiorrhiza and ligustrazine injection (SML) is a type of traditional Chinese medicine injection, which has been considered a promising adjunctive therapy treatment for acute cerebral infarction (ACI). Although there have been positive reports on the treatment of SML, there is still controversy over its exact efficacy and safety in ACI patients. In this study, a systematic review was conducted on randomized controlled trials (RCTs) of SML for the treatment of ACI to evaluate its clinical efficacy and safety.Method: From the establishment of the database until May 2023, all randomized controlled trials related to SML and ACI were collected from the Cochrane Library, Web of Science, Embase, Medline, PubMed, CSJD, Wanfang database, CBM and CNKI. This systematic review and meta-analysis were strictly conducted in accordance with the PRISMA statement.The reported outcomes including overall response (ORR), National Institutes of Health Stroke Scale (NIHSS), hemorrheology indexes, activity of daily living (ADL) and adverse events were in detail investigated.Results: An analysis was conducted on the relevant data of 3869 ACI patients from 38 trials.The results indicated that the combination of conventional treatment and SML can significantly improve the ORR of patients (RR = 1.23, 95% CI = 1.20-1.27, P < 0.00001), neurological status (NIHSS, MD = -4.35, 95% CI = -5.15–3.54, P < 0.00001) and ADL (Barthel Index score, MD = 10.27, 95% CI = 7.75-12.79, P < 0.00001) compared with regular treatment alone. After the combined therapy, the hemorheology of ACI patients also significantly improved (P<0.05). There is no significant difference in the frequency of adverse events between the two groups (RR = 1.49, 95% CI = 0.91-2.46, P = 0.11).4The evidence from the meta-analysis suggested that the combination of conventional therapy and SML is safer and more effective than conventional therapy alone in treating ACI. However, due to the limitations of this analysis, such as regional bias and publication bias, the above conclusions need to be further verified by prospective, high-quality and multicenter clinical trials.